INTEGRASI NILAI PENDIDIKAN ISLAM DAN PENGEMBANGAN KEWIRAUSAHAAN DALAM LINGKUP PENDIDIKAN - Sopian, Mohamad (Institut PTIQ Jakarta, 2025)
This study aims to examine the integration of Islamic educational values in the development of entrepreneurship within the educational sphere. Through a qualitative descriptive literature study approach, this research analyzes various secondary sources such as journal articles and relevant academic books. The findings identify Islamic educational values that have significant relevance to entrepreneurship, including honesty (siddiq), trust (amanah), halal principles, avoidance of riba (usury), leadership, responsibility, hard work, creativity, and innovation. This study also explores strategies for implementing this integration within curricula, teaching methods, training, and entrepreneurship programs in Islamic educational institutions. Additionally, it examines internal and external challenges as well as opportunities in developing entrepreneurship based on Islamic values. The conclusion of this research emphasizes the importance of integrating Islamic educational values and entrepreneurship development in shaping Indonesia's younger generation to be not only morally upright and independent but also to possess a strong entrepreneurial spirit